Recall that **indefinite integral** follows `int f(x) dx = F(x) +C` where:

`f(x)` as the integrand function

`F(x) ` as the antiderivative of `f(x)`

`C` as the constant of integration.

For the given integral problem: `int 2x^3 cos(x^2) dx` , we may apply apply** u-substitution** by letting: `u = x^2` then `du =2x dx` .

Note that `x^3 =x^2 *x ` then `2x^3 dx = 2*x^2 *x dx` or `x^2 * 2x dx`

The integral becomes:

`int 2x^3 cos(x^2) dx =int x^2 *cos(x^2) *2x dx`

`= int u cos(u) du`

Apply formula of **integration by parts**: `int f*g'=f*g - int g*f'` .

Let: `f =u` then `f' =du`

`g' =cos(u) du` then `g=sin(u)`

Note: From the **table of integrals**, we have `int cos(x) dx =sin(x) +C` .

`int u *cos(u) du = u*sin(u) -int sin(u) du`

`= usin(u) -(-cos(u)) +C`

`= usin(u) + cos(u)+C`

Plug-in `u = x^2` on `usin(u) + cos(u)+C` , we get the **complete indefinite integral** as:

`int 2x^3 cos(x^2) dx =x^2sin(x^2) +cos(x^2) +C`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.